Forced Degradation and Stability Testing of Chloramphenicol Ear Drops Using Derivative Spectrophotometry Combining with Chemometrics - Rahmah, Annisa; Wijaya, Triyadi Hendra; Wasito, Hendri (Jurnal Ilmiah Farmasi, 2025)
Background: Chloramphenicol eye drops have a lower stability than solid dosage forms. Hence, it is necessary to assess their stability. One stability test that can be conducted is the forced degradation approach, which involves applying stress conditions that are more severe than those used in accelerated stability testing.Objective: This study used forced degradation to explore the stability profile of chloramphenicol ear drops.Methods: Stability analysis was carried out using a derivative spectrophotometric instrument combined with chemometric analysis. The forced degradation study was conducted by exposing the sample to three conditions: acidic (0.1 N HCl at 80°C for 2 hours), alkaline (0.1 N NaOH at 80°C for 2 hours), and heat (90°C for 4 hours). Principal Component Analysis (PCA) and Partial Least Squares–Discriminant Analysis (PLS-DA) were utilized for the chemometric analysis. Results: Sequential chloramphenicol observations with a zero to third derivative show a maximum wavelength of 278, 260, 234, and 292 nm. According to stability studies with forced degradation, chloramphenicol tended to degrade under alkaline and thermal conditions compared to acidic conditions. A typical grouping pattern amongst forced degradation treatments is revealed by chemometric analysis, which characterizes chloramphenicol's stability profile under different experimental settings.Conclusion: The UV-Vis spectrophotometric approach, both non-derivative and derivative, can describe changes in chloramphenicol degradation profiles, although the specific degradation products generated remain unknown.